Linear isotherm regularities of liquid gallium under pressure - Huaming Li; Hao Ding; Yanting Tian; Yongli Sun; Mo Li (AIP Advances, 2021)
Several new regularities in liquid gallium have been obtained from both the available experimental data and calculated thermodynamic properties along the isothermal lines with the equation of state (EoS) of a power law form. The quantity Z−1V3 is linearly proportional to V3 for all isotherms at high temperatures. Both the calculated reduced isothermal bulk modulus B*=BTVRT and the parameter Zint=PintVRT derived from the available experimental data and EoS of a power law form are observed to be linear with respect to V−3 with the temperature T and gas constant R, which is verified by the derived analytical expression from the derived linear isothermal regularity (LIR) EoS. By using the analytical expression from the LIR EoS, the calculated isobaric thermal expansion coefficient, isochoric heat capacity, isobaric heat capacity, Grüneisen parameter, and Anderson–Grüneisen parameter show quite different behavior with pressure at a constant temperature compared with those values from EoS of a power law form. In addition, analytical expressions of thermodynamic properties of liquid gallium are derived from the LIR EoS, such as adiabatic bulk modulus, sound velocity, entropy, internal energy, enthalpy, Helmholtz free energy, and Gibbs free energy, which have the same tendency with pressure at a constant temperature as the numerically integrated values from EoS of a power law form.